1996
DOI: 10.1038/icb.1996.13
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐Specific apoptosis in immortalized T cells by soluble MHC class II‐peptide complexes

Abstract: SummaryThe recognition of T cell receptors (TCR) by purified major histocompatibility complex {MHC) class Il-peptide complexes in the absence of costimulatory signals leads to the induction of T ceil nonresponsiveness or anergy. In a recent study using human T cell clones, it was observed that prolonged incubation of resting T cells with soluble MHC Il-peptide complexes appears to result in T cell apoptosis. The present study shows that the engagement of TCR by soluble MHC Il-pcptide complexes also results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The transformed SS8T cells utilized in this study have been characterized for their restriction to HLA-DR2 and MBP(84-102) peptide (22). In our laboratory, we have shown that SS8T cells can be equally recognized by DR2 and MBP(83-102)Y 83 peptide (23,29). Results presented in showed no signi cant increase in c -IFN production (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…The transformed SS8T cells utilized in this study have been characterized for their restriction to HLA-DR2 and MBP(84-102) peptide (22). In our laboratory, we have shown that SS8T cells can be equally recognized by DR2 and MBP(83-102)Y 83 peptide (23,29). Results presented in showed no signi cant increase in c -IFN production (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…The transformed SS8T cells utilized in this study have been characterized for their restriction to HLA-DR2 and MBP(84-102) peptide (22). In our laboratory, we have shown that SS8T cells can be equally recognized by DR2 and MBP(83-102)Y 83 peptide (23,29). Results presented in Fig.…”
Section: Resultsmentioning
confidence: 84%
“…In addition, a primary hepatocyte system using enzymatic activity as an endpoint has several problems such as obtaining a stable cell preparation and reproducibility of data. In this study, we designed an in vitro assay for Kupffer cell-mediated cytotoxicity, applying the BrdU-labeled cells used for cytotoxicity assays (Ito et al, 1996;Arimilli et al, 1996). Our assay showed a good correlation between the number of co-cultured Kupffer cells and cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%